The effect of environmental humidity and temperature on skin barrier function and dermatitis - Kristiane A. Engebretsen; Jeanne D. Johansen; Sanja Kežić; Allan Linneberg; Jacob P. Thyssen (2015)
Physicians are aware that climatic conditions negatively affect the skin. In particular, people living in equator far countries such as the Northern parts of Europe and North America are exposed to harsh weather during the winter and may experience dry and itchy skin, or deterioration of already existing dermatoses. We searched the literature for studies that evaluated the mechanisms behind this phenomenon. Commonly used meteorological terms such as absolute humidity, relative humidity and dew point are explained. Furthermore, we review the negative effect of low humidity, low temperatures and different seasons on the skin barrier and on the risk of dermatitis. We conclude that low humidity and low temperatures lead to a general decrease in skin barrier function and increased susceptible towards mechanical stress. Since pro-inflammatory cytokines and cortisol are released by keratinocytes, and the number of dermal mast cells increases, the skin also becomes more reactive towards skin irritants and allergens. Collectively, published data show that cold and dry weather increase the prevalence and risk of flares in patients with atopic dermatitis.